PENGENALAN PERTANYAAN ESENSIAL UNTUK PENGEMBANGAN BAHAN AJAR YANG HOTS KEPADA GURU SEKOLAH DASAR - Winarti, Eny; Kurniastuti, Irine (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
In 21st-century learning, life skills are indicated to be essential. Basic literacy is known to be one of them. Unfortunately, Indonesia is indicated to be low in literacy. Despite the Gerakan Literasi Sekolah [School Literacy Movement] offered by the government, literacy results are still low. This analysis indicated that improvement in Higher Order Thinking Skills (HOTS) is needed. This condition encouraged us to introduce essential questions as a part of language literacy to teachers to develop basic literacy skills. Reviews indicated that essential questions were effective to stimulate HOTS. Adopting educational design research, the researcher provided a diagnostic test to identify teachers’ literacy levels. The diagnostic was then followed by a short workshop to assist teachers to develop learning scenarios with essential questions in it. The learning scenarios developed by teachers suggested the requirement for teachers to have more practice in developing essential questions. Therefore, a module with step-by-step ways to develop essential questions followed by thorough workshops and training needs to be proposed as the follow-up.